Morphological characters and phylogenetic analysis reveal a new species of Sanghuangporus from China - Zhu, Lin; Xing, Jia-Hui; Cui, Bao-Kai (Phytotaxa, 2017)
Based on phylogenetic studies, the Inonotus linteus complex has been recently divided into two genera, Sanghuangporus and Tropicoporus. During investigations on the species diversity of the Inonotus linteus complex from China, a new species, Sanghuangporus quercicola sp. nov., is described based on morphological and molecular data. Morphologically, it is characterized by perennial, pileate basidiomata, a heterogeneous hyphal system with monomitic in context and dimitic in trama, and broadly subglobose to ovoid, thick-walled basidiospores measuring as 3–3.9 × 2.4–2.8 μm. Phylogenetically, the status of S. quercicola is strongly supported based on sequences of the nuclear internal transcribed spacer (ITS) regions.